2020
DOI: 10.1002/prep.201900365
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Combustion Developments of Granular Explosive (RDX/HMX) in Response to Mild‐Impact Loading

Abstract: The experimental analyses of ignition and burning responses of mild‐impacted granular explosive, namely, cyclotrimethylene trinitramine (RDX) and cyclotetramethylene tetranitramine (HMX), were performed based on an optimized drop‐weight system equipped with a High‐Speed Camera (HSC). It has been found that jetting phenomena observed by HSC is the result of the energy released by gaseous products, which push the pulverized or melted explosives to splash radially. Jetting is the only and the most obvious differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Under the same loading conditions, the sample also showed a long-term, large-scale light transmission phenomenon. After the experiment, the researchers observed the wax paper under a microscope and found evidence that the sample melted into the wax paper and solidified in the "groove" of the wax paper [20][21][22]. The experimental process images of 700 μm small particles are very similar to the experimental images of RDX, which have experienced the process of fragmentation, slow radial expansion, and light transmission loading.…”
Section: Resultsmentioning
confidence: 82%
“…Under the same loading conditions, the sample also showed a long-term, large-scale light transmission phenomenon. After the experiment, the researchers observed the wax paper under a microscope and found evidence that the sample melted into the wax paper and solidified in the "groove" of the wax paper [20][21][22]. The experimental process images of 700 μm small particles are very similar to the experimental images of RDX, which have experienced the process of fragmentation, slow radial expansion, and light transmission loading.…”
Section: Resultsmentioning
confidence: 82%
“…Only 1 % of the material particles producing microcracks will significantly promoted the combustion behavior of the sample. SEM analysis results indicated that the combustion rate sensitivity of the DNAN‐based MCEs was directly related to the microstructural damage of the HMX particles [26, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al. [11, 12, 13] modified the traditional drop hammer device and combined with the high‐speed camera to carry out the drop hammer impact loading experiment on HMX, RDX and other energetic particles, and recorded the plastic deformation, melting, ignition, combustion and extinguishing process of energetic particles. The effects of drop weight height and energetic particle looseness on hot spot formation and ignition were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Perry et al [9,10] embedded silica spherical sand particles into the contact surface of energetic materials sample and anvil to prove the conclusion that friction mechanism induces ignition of energetic materials. Wu et al [11,12,13] modified the traditional drop hammer device and combined with the high-speed camera to carry out the drop hammer impact loading experiment on HMX, RDX and other energetic particles, and recorded the plastic deformation, melting, ignition, combustion and extinguishing process of energetic particles. The effects of drop weight height and energetic particle looseness on hot spot formation and ignition were studied.…”
Section: Introductionmentioning
confidence: 99%